2022
DOI: 10.3389/fpubh.2022.1014470
|View full text |Cite
|
Sign up to set email alerts
|

Older age and depressive state are risk factors for re-positivity with SARS-CoV-2 Omicron variant

Abstract: BackgroundThe reinfection rate of SARS-CoV-2 Omicron variant is high; thus, exploring the risk factors for reinfection is important for the effective control of the epidemic. This study aimed to explore the effects of psychological and sleep factors on re-positivity with Omicron.MethodsThrough a prospective cohort study, 933 adult patients diagnosed with Omicron BA.2.2 infection and testing negative after treatment were included for screening and follow-up. We collected data on patients' demographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that diabetes mellitus, as a pro-inflammatory disease, increases the risk of severe SARS-CoV-2 infection and prolonged recovery ( Onder et al., 2020 ; Al-Kuraishy et al., 2021 ). Furthermore, some of the patients were elderly and had multiple chronic comorbidities; they may be susceptible to moderate/severe infection and prolonged recovery time due to poor immunity and pro-inflammatory conditions ( Li et al., 2022 ). Considering that the ACEI/ARB could increase ACE2 expression, we investigated the impact of these antihypertensive drugs on SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that diabetes mellitus, as a pro-inflammatory disease, increases the risk of severe SARS-CoV-2 infection and prolonged recovery ( Onder et al., 2020 ; Al-Kuraishy et al., 2021 ). Furthermore, some of the patients were elderly and had multiple chronic comorbidities; they may be susceptible to moderate/severe infection and prolonged recovery time due to poor immunity and pro-inflammatory conditions ( Li et al., 2022 ). Considering that the ACEI/ARB could increase ACE2 expression, we investigated the impact of these antihypertensive drugs on SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The phases that have been followed in this review are illustrated in Figure 1. carried out in China came to the conclusion that for hospitalized patients who carried the Omicron variant, older age made it more difficult for them to recover from the virus, and along with a depressive status, it constituted a risk factor that could lead to an Omicron re-positivity [14]. One expert review highlights the need for studies that focus on a vulnerable population, such as people that have an older age, comorbidities, or are immunocompromised, as this segment of the population has the highest risk of developing severe outcomes [15].…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to find a solution to this issue taking into consideration the emerging literature that calls attention to the requirement of increasing vaccine dosages in order for the treatment to be effective for the more susceptible members of the population [7][8][9]13]. In addition, a study that was carried out in China came to the conclusion that for hospitalized patients who carried the Omicron variant, older age made it more difficult for them to recover from the virus, and along with a depressive status, it constituted a risk factor that could lead to an Omicron re-positivity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the emergence of SARS-CoV-2 reinfection has become a serious threat and raised new global health concerns. Older adult people, especially those with comorbidities, have a higher risk of acquiring SARS-CoV-2 reinfection (7)(8)(9). Moreover, age is a significant risk factor for COVID-19 progression (3,10,11).…”
Section: Introductionmentioning
confidence: 99%